Air pollution in a tropical city: the relationship between wind direction and lichen bio-indicators in San José, Costa Rica - Neurohr Bustamante, Erich (Universidad de Costa Rica, 2011)
Abstract: Lichens are good bio-indicators of air pollution, but in most tropical countries there are few studies on the subject; however, in the city of San José, Costa Rica, the relationship between air pollution and lichens has been studied for decades. In this article we evaluate the hypothesis that air pollution is lower where the wind enters the urban area (Northeast) and higher where it exits San José (Southwest). We identified the urban parks with a minimum area of approximately 5 000m² and randomly selected a sample of 40 parks located along the passage of wind through the city. To measure lichen coverage, we applied a previously validated 10 x 20cm template with 50 random points to five trees per park (1.5m above ground, to the side with most lichens). Our results (years 2008 and 2009) fully agree with the generally accepted view that lichens reflect air pollution carried by circulating air masses. The practical implication is that the air enters the city relatively clean by the semi-rural and economically middle class area of Coronado, and leaves through the developed neighborhoods of Escazú and Santa Ana with a significant amount of pollutants. In the dry season, the live lichen coverage of this tropical city was lower than in the May to December rainy season, a pattern that contrasts with temperate habitats; but regardless of the season, pollution follows the pattern of wind movement through the city. Rev. Biol. Trop. 59 (2): 899-905. Epub 2011 June 01.Original photographs of lichen communities:https://zenodo.org/record/495481#.WPTTxFPytTVhttps://zenodo.org/record/491601#.WPTTwVPytTVhttps://zenodo.org/record/495478#.WPTTwlPytTV